PENGARUH PENERAPAN SAK EMKM DAN CLOUD ACCOUNTING SERTA BUDAYA ORGANISASI TERHADAP KINERJA UMKM DENGAN KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABLE MODERASI - Yumiko, Yumiko; Tjakrawala, Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to know hows the performance of SMEs that engaged in culinary in Jakarta due Covid-19 and the effect of cloud accountings, SAK EMKM, and organizational culture towards SMEs performance with environment uncertain as moderating effect. Sample was selected using purposive sampling method and the valid data was 184 respondents. Data processing techniques using SmartPLS 3rd version. The result of this study indicate that cloud accounting, SAK EMKM and organizational culture have a positive and significant effect to SMEs performance, and negative significant effect when those independent variables moderates by environment uncertain to SMEs performance. The implication of this study is the important of SAK EMKM, cloud accounting and also organizational culture for SMEs performance with or without environment uncertain.